Prognostic factors for elderly breast cancer patients in University Malaya Medical Centre, Malaysia - Phua, C.E.; Bustam, A.Z.; Yip, C.H.; Taib, N.A. (West Asia Organization for Cancer Prevention, 2010)
Background: Information about elderly breast cancer patients' outcome is limited. This study aimed to evaluate the treatment outcomes in women aged 70 and above with specific analysis on prognostic clinicopathological features and treatment modalities. Materials and Methods: This retrospective study examined breast cancer patients between 1st January 1994 and 31st December 2004 in UMMC. Survival analysis was performed using the Kaplan-Meier method and comparisons between groups using the log-rank test. Univariate and multivariate analysis on prognostic factors were carried out using the Cox's proportionate hazard model for patient demographics, and tumour and treatment factors. Results: One hundred and thirty six patients were identified, with a median age at diagnosis of 75 years. Most had at least one co-morbidity (61.8%). Only 75.0% had a good performance status (ECOG 0-1). Mean tumour size was 4.4cm. Primary tumour stages (T stages) 3 and 4 were present in 8.1% and 30.1% of patients respectively, and 30.9% had stage III and 8.8% had stage IV disease based on overall AJCC staging. ER positivity was 58.1%. PR status was positive in 30.1%. Surgery was performed in 69.1% of the patients and mastectomy and axillary clearance were the commonest surgical procedures (50.7%). Some 79.4% of patients received hormonal therapy, 30.1% radiotherapy and only 3.6% chemotherapy. Non-standard treatment was given to 39.0% of patients due to a variety of reasons. The cumulative 5 years overall, relapse free and cause specific survivals were 51.9%, 79.7% and 73.3% respectively. Performance status, T3-4 tumour, presence of metastasis, tumour grade and ER status were independent prognostic factors for overall survival. For cause specific survival they were T4 tumour, presence of metastasis and ER status. Conclusion: The 5 years overall survival rate was 51.9% and 41.8% of deaths were non-breast cancer related deaths. Low survival rate was related to low life expectancy in this population. Locally advanced disease, metastatic disease and high ER negative rates play a major role in the survival of elderly breast cancer patients in Malaysia.